2D-ERT data for localizing a Black Death mass grave in Erfurt, Thuringia (Germany) - Matthias Silbermann; Marco Pohle; Peter Jung; Ulrike Werban (PANGAEA, 2025)
Near-surface geophysical prospection combined with sediment coring was used to determine the exact location of a Black Death mass grave in Erfurt, Thuringia, Germany. The focus was on exploring the natural stratigraphic and pedogenic environment using sediment coring and geophysical surveys to gain a broader contextual understanding of the site and to determine the most appropriate geophysical methods for locating a mass grave and characterising the natural background. Electrical Resistivity Tomography (ERT) proved to be the most suitable geophysical method. The ERT data were collected by using a PC controlled DC resistivity meter system (RESECS, GeoServe, Kiel, Germany). A total of seven ERT transects were measured, three transects in September 2022, two transects in January 2023 and two transects in June 2023. The electrode spacing was 0.5 m and the transect length varied from 31.5 to 87.5 meter. For the measurements in autumn 2022 we used a Wenner alpha configuration. For the subsequent measurements in 2023, we used Wenner alpha and Dipole-Dipole configuration. The coordinates and the heights of the electrodes in the central wooded area (ERT02, ERT03, ERT04, ERT06 and ERT07) were measured using a total station (Leica TPS1200+). The electrode positions and heights of ERT11 and ERT12 were measured with a differential GPS (Leica GPS1200). Further information on the measurement setup and data structure can be found in the explanation of the specific ERT transects.